Integrated waste management in Sarawak for industry network - Herman Amia, Anak Atek. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Waste is inevitable. Industrial waste of all waste is, pose the most challenging problem to human because of its hazardousness. Sarawak, on the other hand, is an ever-improving state with an enviable richness ofraw material (petroleum, natural gas, mineral, timber etc) and vast industrial parks. Therefore, it is imperative to implement an environmentally sustainable and integrated waste management system to handle the industry's unavoidable by-product, which is waste. This study will attempt to integrate the available waste management option by using the indexing method, with respect to the types of industrial waste being generated in Sarawak. From the indexing of waste management options, it has been found out that the best waste management options are definitely the waste reduction and waste reuse. Waste recycling is also favourable and this compliment the flrst two waste management options to form the 3R practice (reduce, reuse and recycle), which are best implemented at the industry or waste makers itself. Thermal incinerator and landfill should be the final waste options because as soon as waste undergo incineration and landfill, there is lesser possibility of salvaging (recycling) the waste or in other words the waste is lost forever as in the case of landfill.